The other Lata - Ramisetti, Kirthana (GCP, 2025)
"Somewhere in New York City, Lata Murthy knows there is another person with her name living a much more interesting life. That's because Lata often receives the other Lata's emails: invites to Hampton soirees, fundraising appeals from the New York City Ballet and reminders about sample sales at Soho boutiques.. Lata's own life-working in digital content, watching Food Network marathons, spending recklessly on clothes she can't afford-feels pathetic in comparison. So, one day she decides to take on this other Lata's identity and jumps headfirst into the glamorous New York lifestyle ... but not without consequences. At first, it all feels like a fairy tale. Lata learns that the invites were meant for a Mumbai socialite who shares her name, and finds a way to step into the woman's shoes. In doing so, all of Lata's NYC dreams come true: she gets a higher-paying job, moves into a chic Chelsea apartment and is embraced by an elite friend group that includes Rajeev, an up-and-coming fashion designer intent on making a splash at New York Fashion Week. But Lata doesn't just catch the attention of the handsome fashion designer-she also incurs the wrath of the mysterious woman she is impersonating. And this Other Lata wants Lata to pay...but in the oddest of ways. Other Lata's blackmail seems designed to humiliate Lata in front of her wealthy new circle, and Lata has no choice but to submit to her demands if she doesn't want to lose her new friends and lifestyle. Despite Other Lata's machinations, Lata and Rajeev's romance finds ways to blossom. But when Other Lata's demands change from mischievous to illegal, Lata must find a way to extricate herself from Other Lata's control once and for all"--